2021
DOI: 10.1177/03000605211062442
|View full text |Cite
|
Sign up to set email alerts
|

The advanced lung cancer inflammation index predicts outcomes of patients with non-small cell lung cancer following video-assisted thoracic surgery

Abstract: Objective The advanced lung cancer inflammation index (ALI) predicts overall survival (OS) in patients with advanced lung cancer. However, few studies have tested ALI’s prognostic effect in patients with non-small cell lung cancer (NSCLC) following video-assisted thoracic surgery (VATS), especially patients at stage III. This study investigated the relationship between ALI and outcomes of patients with NSCLC following VATS. Methods We retrospectively examined 339 patients with NSCLC who underwent VATS at Hebei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Consistent with previous studies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), our study found that NLR, PLR, LMR, SII, PIV, FAR, FPR, AGR, ALI, PNI, AAPR, CAR, RAR, APR, and FFA/Alb were all associated with OS in the univariate analysis. Even RAR, APR, and FFA/Alb, which were not evaluated in previous lung cancer association studies, were found to be independent predictors of prognosis in patients with NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), our study found that NLR, PLR, LMR, SII, PIV, FAR, FPR, AGR, ALI, PNI, AAPR, CAR, RAR, APR, and FFA/Alb were all associated with OS in the univariate analysis. Even RAR, APR, and FFA/Alb, which were not evaluated in previous lung cancer association studies, were found to be independent predictors of prognosis in patients with NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), our study found that NLR, PLR, LMR, SII, PIV, FAR, FPR, AGR, ALI, PNI, AAPR, CAR, RAR, APR, and FFA/Alb were all associated with OS in the univariate analysis. Even RAR, APR, and FFA/Alb, which were not evaluated in previous lung cancer association studies, were found to be independent predictors of prognosis in patients with NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…The indicators of systemic inflammatory response, including the neutrophil-to-lymphocyte ratio (NLR) (9), the platelet-to-lymphocyte ratio (PLR) (10), the lymphocyte-tomonocyte ratio (LMR) (11), the systemic immune-inflammation index (SII) (12), and the pan-immune-inflammation value (PIV) (13), are significant in determining the prognosis of patients with lung cancer. The fibrinogen-to-albumin ratio (FAR) (14), the fibrinogen-to-prealbumin ratio (FPR) (15), the albumin-toglobulin ratio (AGR) (16), the advanced lung cancer inflammation index (ALI) (17), the prognostic nutritional index (PNI) (18), the albumin-to-alkaline phosphatase ratio (AAPR) (19), and the C-reactive protein-to-albumin ratio (CAR) (20), as well as other inflammatory and nutritional complex indicators, are also biomarkers for predicting the prognosis of lung cancer. Furthermore, red cell distribution width-to-albumin ratio (RAR) (21), alkaline phosphatase-to-prealbumin ratio (APR) (22), free fatty acid (FFA) content (23), and other markers are significant predictors for cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 77 ], multiple studies subsequently confirmed that lower ALI tended to predict poor prognosis in patients with NSCLC [ 78 , 79 ]. Whether receiving targeted treatment [ 80 ], 1st line chemotherapy [ 81 ], radical surgery [ 82 , 83 ], or chemotherapy combined with targeted treatment [ 84 ], ALI shows prognostic value. Even in patients at the early stage of NSCLC, ALI also has a prognostic value [ 85 , 86 ].…”
Section: Albumin-related Inflammation Markers Based On Peripheral Blo...mentioning
confidence: 99%